Sociology Of Law And The Effectivity Of Asean To Prevent Human Security Issues In The Region - Seroja, Triana Dewi; Silviani, Ninne Zahara (JURNAL LEGALITAS, 2022)
Currently there are no indicators that can measure the effectiveness of the role of ASEAN in Southeast Asia, especially those related to human security issues in the safety of labor and migrants' mobilization. However, ASEAN still working through any possibilities of cooperation to prevent any threats that would endanger the personal securities of ASEAN community. This paper will further analyze the human security issues in Southeast Asia starting with conceptualizing, identifying, and engaging to find how is the effectivity of ASEAN in charge of prevent human security issues from sociology of law perspective with normative-juridical methodology combined with perspective of international relation approach. Based on the findings in conceptual and data, this research will show the problems that have been handled and have not been done by ASEAN institutionally. In addition to showing the relevance of the establishment of ASEAN Political-Security Community (APSC) 2015 as an affirmation for all ASEAN member countries to respond to institutional human security issues especially in the mobilization of labor and migrants.